2016
DOI: 10.1186/s12958-016-0219-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of a combination of eight micronutrients versus a standard mono preparation on sperm parameters

Abstract: BackgroundThere are reports showing that l-carnitine alone or in combination with other micronutrients improve sperm parameters. However, comparative studies are still lacking. This study was carried out to compare the short term effects of a combination of eight micronutrients including l-carnitine vs. a mono-substance (l-carnitine alone) on sperm parameters.MethodsThis was a prospective, open-labelled, nonrandomized study that included male subjects (20 to 60 years) with at least 1 year of subfertility and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…15 In contrast, semen volume increased after combined antioxidant treatment for 3 months. 18 Sperm concentration significantly increased after 3 months of combined antioxidant treatment. These results are consistent with previous reports which showed an increment in sperm concentration after antioxidant supplement.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…15 In contrast, semen volume increased after combined antioxidant treatment for 3 months. 18 Sperm concentration significantly increased after 3 months of combined antioxidant treatment. These results are consistent with previous reports which showed an increment in sperm concentration after antioxidant supplement.…”
Section: Discussionmentioning
confidence: 92%
“…These results are consistent with previous reports which showed an increment in sperm concentration after antioxidant supplement. 10,[17][18][19][20] A recent study investigated the effect of combined micronutrients including vitamin E, zinc, selenium, and coenzyme Q10 for 3 months and reported increased sperm concentration in men with infertility. 18 Another study observed higher sperm density in men with idiopathic oligoasthenozoospermia after 6 months of treatment with vitamin E (400 mg/day) with or without clomiphene citrate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 2 non-randomised studies, which were included in this SR [69,74]. We used ROBIN-I, a tool for assessing risk of bias in non-randomised studies of interventions.…”
Section: Robins-imentioning
confidence: 99%
“…We used ROBIN-I, a tool for assessing risk of bias in non-randomised studies of interventions. Risk of Bias assessment of these two studies were judged critical [69,74]. Detailed results are available in Supplementary Table 3.…”
Section: Robins-imentioning
confidence: 99%